Literature Review: Building an Entrepreneurial Spirit - Edi Irawan (International Journal of Scientific Multidisciplinary Research, 2023)
This article aims to review and attempt to inform about the concept of building an entrepreneurial spirit. The research methods used are qualitative and literature study or library research. Based on the results of the discussion, it can be concluded that building an entrepreneurial spirit for beginners requires a mature strategy, one of which is the Contextual Teaching and Learning (CTL) approach. The contextual approach (CTL) is a learning concept that assumes that children will learn better if the environment is created naturally, meaning that learning will be more meaningful if children "work" and "experience" for themselves what they are learning, not just "know it". So that in the end learning is expected to be more meaningful. Then the next step is to build an entrepreneurial spirit through creativity, innovation and motivation. Building entrepreneurship through creativity can be achieved through the ability to think about things in new and unusual ways and produce unique solutions to problems. Then the next step, namely building entrepreneurship through innovation, can be achieved by applying creative solutions to problems and opportunities to improve or enrich people's lives and the process of entrepreneurial innovation is produced from confidence, a clear understanding of goals to generate opportunities. Then the last thing is to build entrepreneurship through motivation, which can be achieved by being able to do something in business